Dream Enactment Behaviour in Post-Traumatic Stress Disorder - Cresta Asah; Hinuga Sandahl; Lone Baandrup; Jessica Carlsson; Poul Jennum (European Journal of Psychotraumatology, 2025)
Background: Sleep disturbances are widely reported in Post-Traumatic Stress Disorder (PTSD). Although Dream Enactment Behaviour (DEB) has long been associated with PTSD, its high prevalence has only recently been recognized, sparking discussions about the classification of trauma-related sleep disorders. The impact of DEB on treatment outcomes in PTSD remains unexplored.Objective: To investigate the role of DEB in functional impairment, symptom severity, subjective sleep disturbances, and treatment response in patients with PTSD, and how it relates to Trauma-Associated Sleep Disorder (TASD).Methods: We analyzed data from a randomized controlled trial carried out in a specialized mental health clinic in Denmark. The trial investigated refugees with PTSD allocated to four groups receiving different combinations of PTSD therapy. Participants completed self-report questionnaires assessing functional impairment, symptom severity, and subjective sleep disturbances, including the REM Sleep Behaviour Disorder Screening Questionnaire (RBDSQ), the Pittsburgh Sleep Quality Index (PSQI), and the Typical Dream Questionnaire (TDQ), at baseline and follow-up. The sample was split into two groups based on the presence of self-reported DEB, and compared at baseline and follow-up. Statistical analyses included chi-square test, Mann–Whitney U test, and regression.Results: A sample of 176 RBDSQ respondents was studied, of which 71% met the criteria for DEB (N = 125). DEB was significantly associated with a poorer treatment response on sleep quality as assessed by the PSQI (N = 122, p = .035), irrespective of treatment group. No differences were observed in functional impairment or symptom severity. Of the 67 TDQ respondents with DEB, 60% did not have trauma-related nightmares (N = 40).Conclusions: DEB is a significant feature of sleep in PTSD and seems to limit the efficacy of treatment interventions. TASD does not encompass all cases of DEB in PTSD and the concept needs further development to be clinically useful.Trail Registration: ClinicalTrials.gov identifier: NCT02761161; clinicaltrials.gov/study/NCT02761161.